Comparison of Transcranial Motor Evoked Potential Amplitude Responses Between Intramuscular and Subcutaneous Needles in Proximal Thigh Muscle. Issue 5 (September 2018) - Gonzalez, Andres A.; Cheongsiatmoy, Justin; Shilian, Parastou; Parikh, Pooja
Abstract : Purpose: Successful intraoperative neurophysiological monitoring is predicated on the presence of adequate baseline–evoked potentials. We have observed that transcranial motor evoked potentials (TcMEPs) yield more robust responses in the distal muscles compared with proximal muscles. One possible explanation is the distance from the needle to the muscle generator. In this study, we investigate whether TcMEP amplitudes from the rectus femoris muscle are affected by changes in needle length. Methods: We analyzed rectus femoris TcMEP responses in surgical patients undergoing lumbar spinal surgery. Needles of two different sizes were placed simultaneously. A shorter 13-mm subcutaneous needle was inserted into the rectus femoris muscle subcutaneous group in addition to a longer 25-mm intramuscular needle (intramuscular group). Each limb was used as an independent control. Transcranial motor evoked potential amplitude responses were obtained using both needles, and statistical analysis was calculated using the Wilcoxon signed-rank test for paired data. Secondary analysis was performed to correlate between TcMEP amplitude and skinfold thickness. Results: Twenty-eight TcMEP responses from the rectus femoris (14 patients) were analyzed. We observed that TcMEP amplitude responses were higher in the intramuscular needle group compared with the subcutaneous group ( N = 28, P < 0.0001). There was a mean difference of 604 μV between the intramuscular versus subcutaneous group (median 184 μV). There was also a significant correlation between TcMEP amplitude and skinfold thickness. Conclusions: Higher TcMEP amplitude responses are seen with longer needles compared with shorter needles placed in the same rectus femoris muscle. Transcranial motor evoked potential baselines may be optimized using longer needles. Skinfold thickness can be a good marker to determine appropriate needle size.